Forensic Application of Cytb and COI Genes for Freshwater stingray Identification: A Seizure Case in Bogotá, Colombia - Lisbeth Gelvez; Ana Cuellar; María Gómez; Jorge Oliveros; Paola Alméciga–Diaz; Myreya Pinedo–Castro; John Infante–González (Revista Científica)
Freshwater stingrays of the Potamotrygonidae family are highly valued in the international market as ornamental fish, leading to growing demand and economic significance. In Colombia, despite legal regulations aimed at protecting these animals and their habitats, the effectiveness of these norms is not always assured. This is partly due to export regulations focusing on morphological criteria for species identification, which may result in inaccuracies, prompting the search for a more precise method based on genetic aspects such as DNA barcoding. This study aimed to assess the potential of the Cytb and COI genes as molecular markers for identifying a species within the Potamotrygonidae family in Colombia using the barcoding technique. DNA was extracted from blood samples of various stingray species from the Puerto Inírida basin, using PCR to amplify specific regions of the COI and Cytb genes, which were then sequenced using the Sanger method. The sequences were read in BioEdit, manually cleaned, analyzed in the BLAST program, and aligned in MEGA, where a neighbor–joining tree was constructed using the Kimura 2– parameter model (K2P). Results indicated no genetic identity between the obtained sequences and the unidentified stingray sequence compared to those in GenBank, nor with other analyzed species, both for COI and Cytb. Phylogenetic analysis showed that the confiscated individual exhibited genetic proximity to Potamotrygon motoro. Additionally, a close genetic relationship between Potamotrygon orbignyi and Potamotrygon schroederi was identified. In conclusion, the phylogenetic method suggests that the seized stingray likely belongs to Potamotrygon motoro. Furthermore, the barcoding method alone is not ideal for identifying species of the Potamotrygonidae family.